Results of the study on principles of brown adipose tissue deposits and characteristics of its fatty acids in pasture sheep lambs (Mongolian Journal of Agricultural Sciences, 2015)
Brown adipose tissue in newborn lambs accounts for 4.52% of total body weight, then during postpartum period it intensively decreases, reaching 1.5% after a week, and finally it is gradually adsorbed or replaced with white adipose tissue. Fatty acids composition of lamb brown adipose tissue includes 17 unsaturated fatty acids (53.23%) and 11 saturated ones (46.95%).Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 38-42